A Multi-Trial Analysis Evaluating the Effects of Pharmacological Levels of IntelliBond Copper on Growing-Finishing Pig Growth Performance and Carcass Characteristics - Hayden R. Kerkaert; Jason C. Woodworth; Joel M. DeRouchey; Steve S. Dritz; Mike D. Tokach; Robert D. Goodband; Hilda Calderon Cartagena (Kansas Agricultural Experiment Station Research Reports, 2023)
A multi-trial analysis was conducted to evaluate the effects of pharmacological levels of added IntelliBond Copper (IBC) on growing-finishing pig growth performance and carcass characteristics compared to pigs fed control diets containing typical additions of copper from a trace mineral premix. Data with 331 observations within 8 trials were included in the final database. Inclusion rates for IBC were either 150 (7 trials), or 200 (1 trial) ppm. Pigs fed IBC throughout the entire grow-finish period had greater (P<0.05) overall ADG, ADFI, and final BW and tended (P= 0.085) to be more efficient than pigs fed control diets. There was no evidence for differences (P>0.10) between dietary treatments for the percentage of pigs marketed. Pigs fed IBC also had (P<0.05) heavier HCW and greater carcass ADG compared to pigs fed a control diet. There were no differences (P>0.10) between pigs fed the control or IBC diets for carcass characteristics, carcass yield, and carcass feed efficiency. In conclusion, the addition of IBC at growth promotion levels throughout the entire growing-finishing period increased final BW, HCW, and ADG on a live and carcass basis.
Keywords: Copper; finishing pigs; tribasic copper chloride